(untitled) (American & British Studies Annual, 2008)
By 1999 when Michael Cunningham published The Hours not many people had known his name although he had already written two other novels. The success of The Hours followed by a movie of same name made Cunningham world-wide known. Soon afterward he himself wrote a screenplay for another movie based upon his earlier novel A Home at the End of the World. This paper deals with some differences between the novels and their film adaptations.